The Facelift and the Wrecking Ball: Urban Renewal and Hamilton’s King Street West, 1957–1971 - Rockwell, Margaret (Urban History Review / Revue d'histoire urbaine, 2009)
AbstractHamilton, Ontario, wanted a modernist makeover for its downtown during the 1960s. Politicians and businessmen aggressively sought federal and provincial urban renewal funds to rebuild the city’s core. This research note focuses on Hamilton’s King Street West, between James and Bay, which ran through the centre of the downtown urban renewal area. The photographs show all that was lost, and the original plan helps us to understand why the people of Hamilton initially accepted the destruction. The resulting traffic corridor was a victory for modernist planners who wanted to remove the pedestrian from the street so that the car could dominate.